12分之5×(5分之12)=(8分之3)÷8分之3=(7分之3)+7分之4=5分之7-(5分之2)
12分之5×()=()÷8分之3=()+7分之4=5分之7-()
2个回答
相关问题
-
4×11分之3÷5分之;4分之3×12分之5÷5分之2 12分之5÷4分之3÷3分之1;5分之3×3分之2+7
-
12分之5-(11分之3—12分之7)= (4分之5—2x8分之3)÷12.5%= 和2-4分之3×3分之5÷6分之5=
-
8分之5-4分之1×9分之8÷3分之2 7分之6×8分之5+8分之3÷6分之7
-
(27分之4+36分之5)÷9分之5 5分之49×8分之7÷7 13÷【(1+3分之1)×4分之3】
-
用你喜欢的方法计算.(8分之7-4分之3)×(9分之8÷3分之1) 12分之5÷(21分之19+7分之3)×5分之1[5
-
简便计算.8分之3+4分之3×12分之7 45×(9分之2+15分之1) (4分之3-8分之5)÷(5分之4×8分之5)
-
(27分之4+36分之5)÷9分之5 5分之49×8分之7÷7 13÷【(1+3分之1)×4分之3】 bangbangw
-
4分之3÷[56×(7分之3-8分之3)] (8分之5+27分之1)×8+27分之19 35÷8分之7×1-7分之2 (
-
简便计算:(1)27÷9分之2×81分之7 (2)12分之5×3分之4+12分之31÷4分之3 (3)7分之5×14分之
-
8分之7×12.5÷24分之7×8